Xylan-degrading ability of thermophilic Actinobacteria from soil in a geothermal area - MAZYTHA KINANTI RACHMANIA; FITRIA NINGSIH; PUTRI PRATIWI SETYANINGSIH; WINDA AYU SYAFITRI; DHIAN CHITRA AYU FITRIA SARI; SHUHEI YABE; AKIRA YOKOTA; ARIYANTI OETARI; Wellyzar Sjamsuridzal (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rachmania MK, Ningsih F, Setyaningsih PP, Syafitri WA, Sari DCAF, Yabe S, Yokota A, Oetari A, Sjamsuridjal W. 2020. Xylan-degrading ability of thermophilic Actinobacteria isolated from soil in a geothermal area. Biodiversitas 21: 144-154. This study was conducted to obtain the potential isolates of xylan-degrading thermophilic Actinobacteria. Seventeen isolates were obtained from the soil samples collected from Cisolok geysers in West Java, Indonesia. These isolates were screened for their xylan-degrading ability on minimal medium with the addition of 0.5% xylan as substrate, and were incubated at various temperatures for 7 days. A total of 15, 14, 4, and 3 isolates showed a xylan-degrading ability at 45°C, 50°C, 55°C, and 60°C, respectively. The three isolates (SL1-2-R-2, SL1-2-R-3, and SL1-2-R-4) that showed xylan-degrading ability at 60°C on 0.5% xylan were further tested by using minimal medium with the addition of 0.1% RBB-xylan as a substrate. The results showed that these isolates were also able to utilized RBB-xylan at 45 to 60°C. The xylanolytic activity of the crude enzymes from the three isolates on minimal medium containing 0.5% xylan or 0.1% RBB-xylan as substrates, indicated that these isolates were able to produce extracellular xylanase. This study revealed that the soil of Cisolok geysers served as an ideal source for finding the thermophilic Actinobacteria which produced xylanase at high temperatures.